The Analysis of CPUE and Factors Affecting the Catch of Tonda Fishing at Bungus Ocean Fishing Port in West Sumatra - Astuti, Indria; Isnaniah, Isnaniah; Zain, Jonny (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
Catch per Unit Effort (CPUE) analysis assesses fishing productivity and indicates fish stock abundance in waters. CPUE values represent the ratio between catch and fishing effort. This study aims to determine CPUE values and analyze the production factors influencing catch. The research method used a survey method with purposive sampling techniques. Data were analyzed using CPUE analysis, multiple linear regression, and classical assumption tests. The results showed that tuna fishing production at PPS Bungus during the 2018–2023 period reached 1,053.09 tons, with catches dominated by skipjack tuna and yellowfin tuna. The highest CPUE value occurred in 2019 at 1.49 tons/trip, and the lowest in 2022 at 0.86 tons/trip. The production factors that significantly influenced catch yields were the number of crew members, engine power, and captain experience, while vessel size and trip duration had a negative influence. The coefficient of determination (R²) value of 0.356 indicates that the research variables only explain part of the variation in catch results. This finding underscores the importance of optimizing production factors and managing fishing efforts to sustain tuna fishing productivity at PPS Bungus